Exigências de manutenção e eficiência de deposição de lisina e treonina para suínos - Ceron, Marcos Speroni (2013)
Two experiments were performed in order to determine the maintenance requirements and marginal efficiency of utilization of the amino acids lysine and threonine, through the nitrogen balance technique. It was used 12 castrated pigs, on each experiment, with an average weight of 52 ± 2 kg (experiment with lysine) and 72 ± 2 kg (experiment with threonine) were kept in metabolism crates in temperature-controlled room of 22 ± 3°C. The pigs were distributed in four diets formulated to supply 30, 50, 60 and 70% of expected standardized digestible lysine requirements and supply 30, 45, 60 and 70% of expected standardized digestible threonine requirements using a changeover design with two periods (seven to adaptation and five collection). All of other essential amino acids were furnished at a minimum of 15% excess level relative to the level of amino acid test. The feed was provided to cover 2.6 times the metabolizable energy requirements needed to maintenance with a daily adjustment according to the expected gain of 0.8 kilograms. The lysine experiment there was no difference (P> 0.00) in dry matter intake (DMI) and metabolizable energy intake (MEI) between treatments. Already in the experiment threonine significant difference was observed of DMI and MEI between treatments. In lysine experiment the amount nitrogen excreted represents on average 46% of the nitrogen ingested with 35% of the nitrogen excreted in feces and 65% in urine. As in lysine experiment the amount nitrogen excreted represents on average 43% of the nitrogen ingested with 35 and 60% of the nitrogen excreted in feces and urine, respectively. The total losses were lysine and threonine 36.4 and 46.3 mg kg-1 BW0.75, respectively, resulting in lysine maintenance requirements of 40.4 mg kg-1 BW0.75 and threonine maintenance requirements of 62.2 mg kg-1 BW0.75. In our experiment the marginal efficiency of lysine and threonine utilization was 90 and 74%, respectively, meaning that 10% of lysine and 26% of intake of standardized threonine was not recovered in the body protein.